2014
DOI: 10.2174/1876388x01406010006
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Tuberculosis Evaluated by Means of 18F-FDG PET/CT: Pilot Study

Abstract: Abstract:Introduction: Spinal tuberculosis is a serious health care problem and diagnosis is often difficult because many diseases may have similar imaging findings. Hence the need to describe findings of spinal tuberculosis with 2-[fluorine 18]fluoro-2-deoxy-D-glucose (FDG) positron emission tomography (PET) when compared to CT. Materials and Methods:Sixteen consecutive patients who underwent 18F-FDG PET/CT and known to have or subsequently were proven to have spinal tuberculosis were analyzed. All patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
(41 reference statements)
2
9
0
1
Order By: Relevance
“…17 It has further been reported that patients with three or more vertebral lesions affected demonstrated intense FDG uptake, almost three times more that of a single spinal lesion. 7 Additionally, in the present study, most participants (80%) in the positive PET/CT scan group were HIV positive, with the majority (60%) having had a history of previous PTB. The relationship between HIV and TB is well known and often described as a co-epidemic, and in 2014 the WHO estimated the risk of contracting TB to be 26 to 31 times greater in HIV-positive individuals.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…17 It has further been reported that patients with three or more vertebral lesions affected demonstrated intense FDG uptake, almost three times more that of a single spinal lesion. 7 Additionally, in the present study, most participants (80%) in the positive PET/CT scan group were HIV positive, with the majority (60%) having had a history of previous PTB. The relationship between HIV and TB is well known and often described as a co-epidemic, and in 2014 the WHO estimated the risk of contracting TB to be 26 to 31 times greater in HIV-positive individuals.…”
Section: Discussionmentioning
confidence: 43%
“…A good example of this is in patients with HIV infection, who, due also to a weaker immune system, have a 20-fold increased risk of contracting TB. 7 Other cytological, microbiological and DNA-based tests are also used in the diagnosis of TB spine. To confirm the diagnosis of spinal TB, it is necessary to either demonstrate acid-fast bacilli (AFB) on microscopy, grow bacilli in culture or have histological evidence of granulomatous inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perasaan takut tertular ini menunjukkan bahwa orang kontak serumah meyakini bahwa mereka mempunyai risiko tertular. Partisipan memahami bahwa risiko merupakan suatu bahaya, kehilangan, kerusakan atau ancaman (Zinn, 2008). Adanya perubahan perhatian dari kerentanan menjadi faktor risiko, ini akan menjadi sumber kesehatan seseorang (Dorthe, dkk., 2009).…”
Section: Pembahasanunclassified
“… 4 These findings suggest that people living with HIV and STB may have less evidence on plain radiography despite more vertebral sites being affected. 9 Antiretroviral therapy (ART) decreases TB risk by 65%. 10 However, immune reconstitution syndrome (IRIS) also plays a role in STB, as those who are unknowingly co-infected and initiating ART, are at risk of developing active symptoms of TB.…”
Section: Introductionmentioning
confidence: 99%